Effectiveness of Neonatal Hearing Screening System: A 12-Year Single Centre Study in the Czech Republic - Blanař, Vít; Škvrňáková, Jana; Pellant, Arnošt; Vodička, Jan; Praisler, Jaroslav; Boháčová, Eva; Dršata, Jakub; Šenkeřík, Marian; Chrobok, Viktor (Journal of pediatric nursing, 2021)
PURPOSE: The study aims to evaluate the number of examined newborns and the results of screening for twelve years (2008-2019) and to assess the effectiveness of the established system of neonatal hearing screening. DESIGN AND METHODS: The study was designed as a retrospective longitudinal data analysis. The data included all the children (19,043) born in the hospital and also children (74) transferred from other healthcare facilities. A total of 19,117 children were included in the research group. RESULTS: In the first three years, a higher number of children did not pass the hearing screening, which was followed by a declining trend in the following years. After the first year of screening (2008), there was an improvement in diagnosis linked with a decrease in false-positive screening results (from 9.4% to 6.4%; p = 0.002). From 2008 to 2015, the ratio of children with positive screening to those with negative screening had a steady or declining trend. CONCLUSIONS: The results showed a reduction in false-positive results after the first year of the screening program, probably due to improved care management and a gradual increase in the skills of the nurses performing the screening. PRACTICE IMPLICATIONS: The cornerstones of neonatal hearing screening are a sufficient number of trained neonatology nurses, their mutual substitutability and the availability of a hearing screening device in the newborn ward every day. The results imply the importance of periodic evaluation of the obtained data, enabling early detection of possible deficiencies in the hearing screening system.
Keywords: Hearing impairment; Hearing Tests; Otoacoustic Emissions, Spontaneous; Permanent hearing loss; dítě; novorozenec; Hearing; Otoacoustic emissions; Neonatal Screening; TEOAE; lidé; Infant, Newborn; retrospektivní studie; Newborn hearing screening; Czech Republic; sluchové testy; Česká republika; otoakustické emise spontánní; Child; novorozenecký screening; Retrospective Studies; sluch; Humans